Panopticon - Yates, Michael D. (Monthly review (New York. 1949), 2022)
Capitalism's two main underpinnings are control and exploitation/expropriation. While there are many sites of control they are all generally supportive of the interests of capital, namely, the endless drive to accumulate wealth. They all help to ensure that we behave so that the system continues to reproduce itself. Since workplaces are the sites where profits are extracted from our labor, it is here that control is most critical.